(untitled) (Scholars’ Journal, 2022)
Language and culture are interrelated. Culture finds its expression in language; so, learning a new language without familiarity with its culture remains incomplete. English speakers at present have dual challenges: one to be able to adopt in world cultures and to promote their local culture in comparison to other cultures. The main purpose of this study is to explore lived experiences of University Level English teachers regarding the promotion of intercultural communication in English Language Teaching classes. The researcher has applied interpretive paradigm, phenomenology as the research design under qualitative research method. Four English language teachers from central campus, Far Western University are the informants for the study. As the data collection tools, in depth interview and personal narratives have been used. The participants are found positive in the promotion of intercultural communication through English language teaching as well as in promoting their local cultures. The study will be useful for teachers, students, curriculum designers, as well as researchers.